Validity of the Child Facial Coding System for the Assessment of Acute Pain in Children With Cerebral Palsy. (April 2016) - Hadden, Kellie L.; LeFort, Sandra; O'Brien, Michelle; Coyte, Peter C.; Guerriere, Denise N.
The purpose of the current study was to examine the concurrent and discriminant validity of the Child Facial Coding System for children with cerebral palsy. Eighty-five children (mean = 8.35 years, SD = 4.72 years) were videotaped during a passive joint stretch with their physiotherapist and during 3 time segments: baseline, passive joint stretch, and recovery. Children's pain responses were rated from videotape using the Numerical Rating Scale and Child Facial Coding System. Results indicated that Child Facial Coding System scores during the passive joint stretch significantly correlated with Numerical Rating Scale scores ( r = .72, P < .01). Child Facial Coding System scores were also significantly higher during the passive joint stretch than the baseline and recovery segments ( P < .001). Facial activity was not significantly correlated with the developmental measures. These findings suggest that the Child Facial Coding System is a valid method of identifying pain in children with cerebral palsy.